Meningkatkan Hasil Belajar Matematika Dengan Model Cooperatif STAD Pada Siswa Kelas V SD Negeri 001 Rambah Hilir Tahun Pelajaran 2015/2016 - Aisyahnum Aisyahnum (STKIP Rokania Pasir Pangaraian, 2018)
Abstract, Mathematics is a science that has an important role in various disciplines and in promoting human fikir power. Therefore, developing love of mathematics students is very important. Today it is often encountered students who do not have the readiness preparedness for learning, especially in math due to the student does not understand the material that has been described by the teacher. This type of research is classroom action research which consist of planning, implementation, observation and reflection. Do the planning stages of the election materials, designing lesson plans and assessment. The implementation stage of the research done at three stages, initial activity, core activities and closing activity. Phase observations were made to observe the behavior of students during the learning process is aided by the observer. Phase reflections do see progress on implementation and make conclusions to determine the deficiency or excess during the learning process. This study consisted of two cycles consisting of two meetings in each cycle. Data analysis techniques by observing the student activity and student learning outcomes. The results of the study in the first cycle of meeting 1 gained an average of 23% of student success, the first cycle of meetings 2 gained an average of 50% of student success. As for Cycle II meeting 1 gained an average of 73% of student success, the second cycle of meeting 2 gained an average of 85% of student success. It is concluded that that the characteristics of student learning are not the same. We as teachers are indeed our duty of this nation's intellectual life, we must not stop thinking to achieve new innovation in order to teach us at any basic competence, the better.the model cooperatif STAD is very supportive once to understand math perform integer arithmetic operations in problem solving